Tribological properties of borate ionic liquids with low corrosion grade and excellent thermal stability in 500 N base oil. (22nd April 2022) - Wang, Feiming; Gao, Xing; Zang, Shuliang; Deng, Guichun; Yue, Shuang
Abstract: Two borate ionic liquids 1‐Butyl‐3‐(2‐methoxy‐2‐oxoethyl)‐imidazole bis(mandelato)‐borate [MABIM][BMB]) and 1, 3‐Dioctylbenzotriazole bis(mandelato)‐borate ([DOBI][BMB]) were synthesised and utilised as the lubricating additives. Their corrosion degrees were measured and the results show that [DOBI][BMB] and [MABIM][BMB] exhibit remarkable anti‐corrosion properties ([DOBI][BMB]: 1a, [MABIM][BMB]: 1b). The 4‐ball machine was employed to evaluate their tribological properties in 500 N base oil. When [DOBI][BMB] and [MABIM][BMB] were added at the concentration of 3.0 wt%, the friction coefficient of 500 N was reduced by 37.5% and 29.5%. It can be concluded from the results of XPS and SEM that a lubricating film containing iron oxide, B2 O3 and organic N‐containing compounds have formed. And a model is proposed so as to describe the lubricating mechanism.